Perbandingan Pengurusan Masa Bekerja di Antara Pengurus di Sektor Awam dan Pengurus di Sektor Swasta - Salma Alwani, Mohd. Sidique (2003)
Generally, the objective of this research was to study the difference of works time management between two sectors, the public and the private sector which were Pejabat Tanah Jajahan Kota Bharu and Kota Bharu branch of Maybank respectively. This research focused on four major aspects that affect work time management in both sector. The four major factors were demographic factors (sex, age, race, married status, academic level and occupational level), attitudes (procrastination, unstrict decision making, no delegation of work, communication weakness and unplanned work task), duty or responsibility (workload, meeting responsibility and responsibility of appointment) and the use of material (using official letter and the use of telephone). This research also focused on the scenario of work time management in public and private sector and both sector in comparison. Method of gathering data was by questionnaire distribution.